Kata al-Ikhlash dalam Alquran: Kajian Semantik - Rahman, Miftahur (AL QUDS : Jurnal Studi Alquran dan Hadis, 2018)
This paper discusses the term khalasha and its derivation in the Quran. This study uses the semantic theory of the Quran Toshhiko Izutsu. First, discuss the basic and relational meaning. Second, perform syntactic and paradigmatic analysis. Third, perform synchronic and diachronic analysis of the term khalasha. Synchronic and diachronic analysis discusses the term from pre-Quran, Quranic (revelation) era, until post-Quran era. Fourth, find weltanschauung the use of khalasha and its derivation in the Quran. The result of this research is the basic meaning of khalasha is pure. The relational meaning is purifying, special, clean, jarring, and clear. There are two different concepts of the use of the khalasha term and its derivation in the Quran. First, the term includes about the concept of religion which means to keep religion. Second, if connected with a thing then its meaning is clean.